Turizam i povezanost otočja - MIČETIĆ, Vinko (Promet - Traffic&Transportation, 2026)
TOURIST TRADE AND ISLAND TRAFFIC LINKS The author reiterates the significant aspect of the islands for the development of tourist industry and deals with the issue of providing adequate traffic links between individual islands and with the inland region. The paper puts an accent on the temporal variations of demand in conjunction with respective information on passenger numbers per months, and seasonal variations in tourist transport services. The author reviews the current situation in the light of substitution of non-profitable services and proposes measures for improved profitability of coastal transport.